Oszacowanie Energii Dysypowanej w Procesie Deformacji Plastycznej Niektórych Metali - Klepaczko, J. (Engineering Transactions, 1967)
As a result of the present analysis relations are obtained enabling an estimation of the energy dissipated in the course of a plastic strain process of some metals at various strain rates and various temperatures. Numerical computations and experiments have been performed for two metals: copper and aluminium. As a result of the experiments it is found that the agreement between the estimations with the values obtained by experiment is good. In the next part of the paper relations are given enabling an estimation of the energy in the case of a metal element deformed to a certain value of strain ϕw at a given strain rate ηw and a given temperature Tw the deformation being continued then at a different strain rate Na and a different temperature Ta.The study of this problem enables, for instance, the estimation of the impact energy of a metal which was subjected to initial static strain.